The Use of Ihtiyat Data in Prayer Time Hisab: Perspectives on Islamic Law - Mujab, Sayful; Shabir, Muslich (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2022)
The Salat in Islam cannot be separated from the time of Salat. Although the procedure for determining Salat times is not explained detailly in the Qur'an, doing Salat should not be arbitrary, especially regarding time. One of the important elements in determining Salat times, one of which is data of ihtiyat. Addition the data of ihtiyat is purpose the calculation results can cover the areas around the markaz. This study reveals a perspective of Islamic law on the addition the data of ihtiyat in determining the initial Salat time. The use of ihtiyat time is very important for anyone who does the reckoning at the time of Salat. However, in Islamic law, there is no legal certainty and there are no scholars who specifically discuss this matter. In a review of Islamic law, the time of ihtiyat in a review of Islamic law can be categorized as wasilah for the purpose that it is a condition of Salat. And it is knowing the time of Salat. Therefore, using ihtiyat time can be categorized in mandatory law because it is a means of something that is obligatory while there is no specific argument for its use. The use of ihtiyat time is in order to accommodate the interests of Muslims who are in certain areas that have a relatively wide expanse.